The molecular mechanisms of fluoroquinolone resistance found in rectal swab isolates of Enterobacterales from men undergoing a transrectal prostate biopsy: the rationale for targeted prophylaxis - Katarzyna Piekarska; Katarzyna Zacharczuk; Tomasz Wołkowicz; Mateusz Mokrzyś; Natalia Wolaniuk; Magdalena Nowakowska; Stanisław Szempliński; Jakub Dobruch; Rafał Gierczyński (BMC, 2021)
Abstract Background Transrectal ultrasound-guided prostate biopsy (TRUS-Bx) is considered an essential urological procedure for the histological diagnosis of prostate cancer. It is, however, considered a "contaminated" procedure which may lead to infectious complications. Recent studies suggest a significant share of fluoroquinolone-resistant rectal flora in post-biopsy infections. Methods The molecular mechanisms of fluoroquinolone resistance, including PMQR (plasmid-mediated quinolone resistance) as well as mutation in the QRDRs (quinolone-resistance determining regions) of gyrA, gyrB, parC and parE, among Enterobacterales isolated from 32 of 48 men undergoing a prostate biopsy between November 2015 and April 2016 were investigated. Before the TRUS-Bx procedure, all the patients received an oral antibiotic containing fluoroquinolones. Results In total, 41 Enterobacterales isolates were obtained from rectal swabs. The MIC of ciprofloxacin and the presence of common PMQR determinants were investigated in all the isolates. Nine (21.9%) isolates carried PMQR with qnrS as the only PMQR agent detected. DNA sequencing of the QRDRs in 18 Enterobacterales (E. coli n = 17 and E. cloacae n = 1) isolates with ciprofloxacin MIC ≥ 0.25 mg/l were performed. Substitutions in the following codons were found: GyrA-83 [Ser → Leu, Phe] and 87 [Asp → Asn]; GyrB codon-605 [Met → Leu], ParC codons-80 [Ser → Ile, Arg] and 84 [Glu → Gly, Met, Val, Lys], ParE codons-458 [Ser → Ala], 461 [Glu → Ala] and 512 [Ala → Thr]. Six isolates with ciprofloxacin MIC ≥ 2 mg/l had at least one mutation in GyrA together with qnrS. Conclusions This study provides information on the common presence of PMQRs among Enterobacterales isolates with ciprofloxacin MIC ≥ 0.25 mg/l, obtained from men undergoing TRUS-Bx. This fact may partially explain why some men develop post-TRUS-Bx infections despite ciprofloxacin prophylaxis.